2006
DOI: 10.1038/sj.ejcn.1602440
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum vitamin D insufficiency and secondary hyperparathyroidism in healthy Danish women

Abstract: Objective: To examine vitamin D status and parathyroid function in normal Danish women postpartum. Design: Three cross-sectional measures during follow-up of 89 women postpartum. Subjects and intervention:We assessed vitamin D status by measuring plasma 25-hydroxyvitamin D (P-25OHD) and the degree of secondary hyperparathyroidism by measuring plasma parathyroid hormone (P-PTH) in 89 Caucasian women at three consecutive visits: (mean (range)) 23 (10-37) days (spring), 117 (95-140) days (late summer) and 274 (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(41 reference statements)
3
6
1
Order By: Relevance
“…This is in accordance with the findings in normal Danish individuals (33), in Danish lactating women (34), and in Danish patients with PHPT (6). In the latter study, plasma 25OHD covariated with monthly sun hours and satellite-based estimation of monthly UV exposure.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in accordance with the findings in normal Danish individuals (33), in Danish lactating women (34), and in Danish patients with PHPT (6). In the latter study, plasma 25OHD covariated with monthly sun hours and satellite-based estimation of monthly UV exposure.…”
Section: Discussionsupporting
confidence: 80%
“…The usually observed inverse hyperbolic relationship between 25OHD and plasma PTH (33,34,39,40) could not be retrieved in the present FHH population in contrast to the findings in the PHPT population. Other studies support that PTH varies inversely with vitamin D status in PHPT patients (6,8).…”
Section: Discussioncontrasting
confidence: 55%
“…Our study also reports higher prevalence of vitamin D deficiency in Indian postpartum women in line with other studies [31][32][33][34]. In a Danish study, Møller et al also reported higher prevalence of vitamin D deficiency along with secondary hyperparathyroidism around 1 year postpartum, although the incidence was lower than that in our study population [35].…”
Section: Discussionsupporting
confidence: 91%
“…20,21 Accordingly, pregnant and breastfeeding women in Scandinavia are recommended to use a daily supplement of 10 mg (400 IU) of vitamin D. 22,23 Furthermore, it is recommended that children aged 2 weeks to 2 years receive a daily supplement of 10 mg of vitamin D. 22,23 Whether these recommendations are adequate is still uncertain, as recent studies have suggested that the supplement should be increased to 25-100 mg per day. 5,20,[24][25][26][27][28] In a population-based cohort study, we aimed at the following: (1) to investigate the prevalence of vitamin D deficiency and insufficiency in Caucasian infants and their mothers at birth and 4 and 9 months after birth; (2) to identify determinants of maternal and infant vitamin D status and to appraise associations between vitamin D status in the newborn children and their mothers; (3) to investigate interactions between plasma 25-hydroxyvitamin D (25OHD) and parathyroid hormone (PTH) levels; and (4) to assess the influence of plasma 25OHD and PTH levels on infant body weight and growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Pregnant and lactating women and their newborn infants are at a high risk of vitamin D deficiency. [3][4][5][6][7][8][9][10][11][12] Vitamin D is involved in skeletal homeostasis during pregnancy. 13,14 Severe vitamin D deficiency with profound hypocalcemia may lead to seizures in neonates, and has also been associated with low birth weight, prenatal death, preeclampsia and an increased risk of primary cesarean section.…”
Section: Introductionmentioning
confidence: 99%